The strongest magnetic fields in the universe: how strong can they become? - Treumann, Rudolf A.; Baumjohann, Wolfgang; Balogh, André (Frontiers in Physics, 2014)
Magnetic fields in the universe are in general weak, of the order of μGauss only. However, in compact objects they assume extraordinarily large values. These are produced by gravitational collapse of massive magnetized objects. Clearly, fields in the massive progenitor are energetically limited by the available energy which can be fed into the generation of currents and magnetic fields. However, when collapsing down to small scales magnetic fields become superstrong exceeding any limits which can be reached in the laboratory. A brief review and discussion is given on the absolute limitation to the magnetic field strengths which can be obtained during such collapses.